2012
DOI: 10.1007/s00223-012-9585-6
|View full text |Cite
|
Sign up to set email alerts
|

Mid-Thigh Cortical Bone Structural Parameters, Muscle Mass and Strength, and Association with Lower Limb Fractures in Older Men and Women (AGES-Reykjavik Study)

Abstract: In a cross-sectional study we investigated the relationship between muscle and bone parameters in mid-thigh in older people using data from a single axial computed tomography (CT) section through the mid-thigh. Additionally we studied the association of these variables with incident low trauma lower limb fractures. A total of 3762 older individuals (1838 men and 1924 women) age 66-96 years, participants in the AGES-Reykjavík Study, were studied. The total cross-sectional muscular area and knee extensor strengt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
35
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 43 publications
(56 reference statements)
4
35
1
2
Order By: Relevance
“…There was no change in thickness, number, and separation of trabeculae in r-irisin-treated compared with control mice. Although it remains unclear why osteoblasts at cortical surfaces will behave differently from those synthesizing trabecular bone, our observation is in line with data indicating greater sensitivity of cortical bone to anabolic factors released by muscle (26,27,35). The selective action of r-irisin on cortical bone is likely to be related to the different functionalities of cortical and trabecular bone.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…There was no change in thickness, number, and separation of trabeculae in r-irisin-treated compared with control mice. Although it remains unclear why osteoblasts at cortical surfaces will behave differently from those synthesizing trabecular bone, our observation is in line with data indicating greater sensitivity of cortical bone to anabolic factors released by muscle (26,27,35). The selective action of r-irisin on cortical bone is likely to be related to the different functionalities of cortical and trabecular bone.…”
Section: Discussionsupporting
confidence: 89%
“…Specifically, by distributing bone mass away from the center, enlarged bone perimeter and cross-sectional area both contribute to increased pMOI and resistance to bending. The effect of r-irisin, essentially mimicking the effect of mechanotransduction (25)(26)(27), thus allows bone to become structurally more efficient for bending and torsion. Indeed, both mouse (28)(29)(30) and rat (31-34) models have collectively shown positive associations between exercise and increased bone size and bone mass.…”
Section: Discussionmentioning
confidence: 99%
“…However, this is also in line with previous literature data reporting that cortical bone is more sensitive to myokines or other anabolic factors released by muscle. [25][26][27] Notably, change in the expression myostatin, also released from skeletal muscle, undergoes opposite direction to Irisin release following exercise, as it has been shown that myostatin signaling is inhibited by acute resistance exercise. 28 In addition, myostatin knock out mice displayed BATexpansion, an effect mediated by the AMPK-PGC1a-FNDC5 pathway in skeletal muscle.…”
Section: Irisin the Messenger Of Healthy Bone-muscle Unitmentioning
confidence: 99%
“…5,7,26,27 Þetta hlutfall kvenna er þó heldur laegra ef borið er saman við eldri íslenska rannsókn þar sem hlutfallið var 72% 28 og rannsóknir frá Noregi og Danmörku þar sem hlutfallið var 71% 7 og 72% 5 , en sambaerilegt við tölur frá Svíþjóð, eða 67%. 29 Meðalaldur sjúklingahópsins var 82 ár sem er sambaerilegt við erlendar rannsóknir.…”
Section: Umraeðaunclassified
“…24 Þetta er þó nokkru haerra en í nokkrum nýleg-um erlendum rannsóknum þar sem dánartíðnin var 16-21% (tafla I). 3,26,27 Það var ekki marktaekur munur á dánartíðni milli kvenna og karla eins og sést í erlendum rannsóknum þar sem dánartíðni er haerri hjá körlum. ójafnvaegi í lengd sjúkrahúsdvalar milli sjúklingahópa sem koma að heiman og frá hjúkrunarheimilum og gaeti það hugsanlega haft áhrif á dánartíðni hér á landi ári eftir mjaðmarbrot.…”
Section: Umraeðaunclassified